A SYSTEMATIC LITERATURE REVIEW: PENERAPAN TEORI PERMAINAN DALAM STRATEGI PROMOSI UNTUK MENGOPTIMALKAN PENJUALAN PRODUK: Systematic Literature Review: Application Of Game Theory In Promotional Strategies To Optimize Product Sales - Nasution, Afifah Nabila; Rambe, Ahmadsyah Fauzian; Fitriani, Fitriani; Nasution, Lilis Suryani; Nasution, Sarmila Fitri Yanti; Sastika, Weni; Ginting, Siti Salamah Br (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
The relevance of Game Theory in promotional strategies is increasing in today's digital era, where information spreads rapidly and competition is increasingly intense. Companies need to consider various factors, including changing consumer preferences, dynamic competitor strategies, and fluctuating market trends. Game Theory provides a strong foundation for this strategic analysis, and enables companies to make more informed and precise decisions. To study further, the researcher used the Systematic Literature Review Method by using a literature review that involves the process of identification, assessment, evaluation, and interpretation in detailing the findings of various relevant studies. This data analysis was carried out to develop an understanding of game theory in product promotion strategies. And based on the results of the analysis of the 20 articles discussed, it turns out that the Application of Game Theory in Promotion Strategies to optimize product sales has a significant impact on sales of a product. Thus, it can be concluded that game theory can be used as a tool in decision making for companies.